Revised stratigraphy of the Tertiary deposits of Istanbul and their engineering properties - Yildirim, Mustafa; Tonaroglu, Murat; Selcuk, Murat E.; Akguner, Cem (SPRINGER HEIDELBERG, 2013)
For over 50 years, the Upper Oligocene-Upper Miocene sedimentary sequence in Istanbul has been considered to be formed of two distinct sequences separated by an unconformity. However, recent field observations and an analysis of numerous borehole data indicate the GurpA +/- nar, Cukur double dagger eAYme and Gungoren Formations are in fact a single sequence of alternating clay-sand/sandstone beds/lenses, here named the AvcA +/- lar Formation. The BakA +/- rkoy Formation, which is typically composed of carbonate rocks, conformably overlies the AvcA +/- lar Formation. The paper provides the geotechnical parameters of the units within the AvcA +/- lar Formation which it is hoped will facilitate selecting suitable geotechnical and engineering geological parameters to represent the deposits and minimize errors in the interpretation/evaluation of in-situ conditions.
Keywords: Stratigraphy; Tertiary; Istanbul; Avcilar formation; Geotechnical properties; MICROZONATION; Engineering; Geology